2021
DOI: 10.1016/j.ahjo.2021.100044
|View full text |Cite
|
Sign up to set email alerts
|

STEMI care 2021: Addressing the knowledge gaps

Abstract: Tremendous progress has been made in the treatment of ST-segment elevation myocardial infarction (STEMI), the most severe and time-sensitive acute coronary syndrome. Primary percutaneous coronary intervention (PCI) is the preferred method of reperfusion, which has stimulated the development of regional STEMI systems of care with standardized protocols designed to optimize care. However, challenges remain for patients with cardiogenic shock, out-of-hospital cardiac arrest, an expected delay to reperfusion (>120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
“…National and local actions to mitigate the pandemic, such as lockdown restrictions, social isolation with substantial fear of infection, and deferral of routine health care, subsequently resulted in unintended consequences in STEMI care 21,22 . There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door‐to‐balloon and total ischemic times, and increased risk of mechanical complications 21–26 . In parallel, we observed a remarkable increase in late presenters (almost doubled) during the early phase of the Covid‐19 pandemic in 2020.…”
Section: Discussionmentioning
confidence: 74%
“…A STEMI is the most severe heart attack because it obstructs one or more coronary arteries, and blocks blood flow to the heart. STEMI can result in more long‐term heart disease and increase the risk of death in patients in the short term 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…STEMI can result in more long-term heart disease and increase the risk of death in patients in the short term. 5,6 Low-and middle-income nations account for at least threequarters of CVD deaths worldwide. People in low-and middleincome nations have less access to primary health care for the early detection and treatment of CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…ST-segment elevation myocardial infarction (STEMI) is the most severe type of heart attack [ 1 ]. It remains the most common cause of death in adults globally [ 2 ].…”
Section: Introductionmentioning
confidence: 99%